A rare case of cerebrospinal fluid rhinorrhea post external dacryocystorhinostomy surgery - Chandana Chakraborti; Nabanita Barua; Kumaresh Chandra; Rosy Kahakashan Christi (Journal of Clinical Ophthalmology and Research, 2016)
Cerebrospinal fluid (CSF) leakage is an uncommon but significant complication of orbital and rarely lacrimal surgery. We report a rare case of CSF rhinorrhea following external dacryocystorhinostomy (DCR) surgery. A 38-year-old healthy lady was diagnosed to have chronic dacryocystitis for which right side external DCR was done. At the evening of first postoperative day, the patient noticed a discharge of clear fluid coming through the right nostril, in sitting posture. The fluid was sent for biochemical analysis. Based on clinical and biochemical tests of fluid, a diagnosis of iatrogenic CSF rhinorrhea was made. Contrast enhanced computed tomography and computed tomography cisternography failed to reveal any site of active leakage. However, the patient improved with conservative management only. CSF leakage occurs very rarely in external dacryocystorhinostomies with only a few case reports found in the literature. Knowledge of anatomy and thorough preoperative assessment may predict areas at high-risk for encountering this problem.